OSTEOSYNTHESIS OF FRACTURES NECK FEMUR: A SYSTEMATIC REVIEW - Susilo, Dhanang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: US hip fractures exceed 250,000 each year. Femoral neck and intertrochanteric fractures are equally diagnosed. This number will double by 2050. Cannulated screws, hip screw systems, proximal femur plates, and cephalomedullary nails can treat femoral neck fractures. These procedures are evaluated for biomechanical stability.  The aim: This article discusses osteosynthesis in patients with femoral neck fractures. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 123 articles, whereas the results of our search on SagePub brought up 72 articles. The results of the search conducted for the last year of 2013 yielded a total 75 articles for PubMed and 16 articles for SagePub. In the end, we compiled a total of 24 papers, 17 of which came from PubMed and seven of which came from SagePub. We included five research that met the criteria.